Land management explains major trends in forest structure and composition over the last millennium in California's Klamath Mountains - Knight, Clarke A; Anderson, Lysanna; Bunting, M. Jane; Champagne, Marie; Clayburn, Rosie M; Crawford, Jeffrey N; Klimaszewski-Patterson, Anna; Knapp, Eric E; Lake, Frank K; Mensing, Scott A; Wahl, David; Wanket, James; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
For millennia, forest ecosystems in California have been shaped by fire from both natural processes and Indigenous land management, but the notion of climatic variation as a primary controller of the pre-colonial landscape remains pervasive. Understanding the relative influence of climate and Indigenous burning on the fire regime is key because contemporary forest policy and management are informed by historical baselines. This need is particularly acute in California, where 20th-century fire suppression, coupled with a warming climate, has caused forest densification and increasingly large wildfires that threaten forest ecosystem integrity and management of the forests as part of climate mitigation efforts. We examine climatic versus anthropogenic influence on forest conditions over 3 millennia in the western Klamath Mountains—the ancestral territories of the Karuk and Yurok Tribes—by combining paleoenvironmental data with Western and Indigenous knowledge. A fire regime consisting of tribal burning practices and lightning were associated with long-term stability of forest biomass. Before Euro-American colonization, the long-term median forest biomass was between 104 and 128 Mg/ha, compared to values over 250 Mg/ha today. Indigenous depopulation after AD 1800, coupled with 20th-century fire suppression, likely allowed biomass to increase, culminating in the current landscape: a closed Douglas fir–dominant forest unlike any seen in the preceding 3,000 y. These findings are consistent with precontact forest conditions being influenced by Indigenous land management and suggest large-scale interventions could be needed to return to historic forest biomass levels.
Keywords: Indigenous management; Forest biomass; Restoration; Carbon policy; Land use